Exposure to fine, ultrafine particles and black carbon in two preschools in nur‐sultan city of kazakhstan. (28th January 2021) - Amouei Torkmahalleh, Mehdi; Zhigulina, Zhuldyz; Madiyarova, Tomiris; Turganova, Kamila; Adotey, Enoch K.; Sabanov, Sergei
Abstract: Children in preschools were studied as an exceptionally vulnerable group to lung diseases due to their immature immune system. Few data are available in the literature addressing the exposure of children in preschools to ultrafine (>10 nm) particles. Exposure of children to fine, ultrafine (10 nm–1 µm) particles and black carbon particles present inside and near two preschools in Nur‐Sultan, Kazakhstan, during Fall 2019 was investigated. For Preschool I, the average daily (6 h) indoor (outdoor) PM1, PM2.5, and PM10 concentrations over three‐week measurements were 15.0 (SD 12.5) µg/m 3, 34.6 (SD 35.1) µg/m 3, and 47.2 (SD 45.2) µg/m 3, respectively. Average indoor UFP concentrations (>10.0 nm) including candle burning events were 5.20 × 10 3 (SD 8.80 × 10 3 ) particles/cm 3, with the background UFP concentration to be 3.30 × 10 3 (SD 1.80 × 10 3 ) particles/cm 3 . In Preschool II, the average UFP concentration (>30.0 nm) in the morning and afternoon was 3.94 × 10 3 (SD 5.34 × 10 2 ) and 3.36 × 10 3 (SD 1.90 × 10 3 ) particles/cm 3, respectively. Indoor black carbon (BC) concentrations were correlated with the outdoor smoking activity. The major sources of the indoor particles in the preschools were dust resuspension, candle burning, and infiltrated outdoor particles.